PENGARUH KUALITAS PRODUK, CITRA MEREK DAN PROMOSI PENJUALAN DALAM PENGAMBILAN KEPUTUSAN PEMBELIAN PRODUK MIE SEDAAP - Nurul Setyaningrum; Handoyo Djoko Waluyo; Andi Wijayanto (Jurnal Ilmu Administrasi Bisnis, 2014)
Instant noodles is a product that is preferred by consumers in the world because of practicality. It is therefore necessary for the company to analyze consumer behavior to determine the product purchase patterns.This research was aimed determine the influence quality of products, brand image, and sales promotion on consumer purchasing decisions of product Mie Sedaap in Kecamatan Tembalang. Population of this research are the consumers who buy and consume the product in the Mie Sedaap Kecamatan Tembalang. Total sample of 100 respondent by using multi stage sampling. The measurement scale using Likert. The data analysis using simple linear regression.Results of this study concluded that the quality of products, brand image and sales promotion have an influence on purchasing decisions. Products quality, brand image and sales promotion variables were able to explain 76.3% of purchasing decisions which have a significant influence on of products quality as big as 59.5%, brand image as big as 73.8%  and sales promotion as big as 48.7%. Product quality, brand image, and sales promotion are concurrent significant influence on purchasing decisions Mie Sedaap in Kecamatan Tembalang.